SECOND LANGUAGE ACQUISITION: RECONCILING THEORIES - Darman Pangaribuan; Jonris Tampubolon (Journal of Applied Linguistics, 2022)
This article makes the case that earlier explanations of SLA shouldn't be discounted. Instead, when combined, they offer a more comprehensive and in-depth understanding of the acquisition process. The ability of second language acquisition (SLA) to naturally adjust to various situations present in both internal and external settings provides evidence in favor of the assertion that SLA is a sophisticated adaptive system. On the basis of this comprehension, frequently debated second language theories, such as behaviorism, will be viewed as explanations for individual components of SLA. Excerpts from a few English language learning histories are given as examples of how students explain their learning processes in order to support this idea. The last assertion is that SLA should be seen as a chaotic/complex system. Keywords: Second Language Acquisition; Language Learning Histories